THE INFLUENCE OF FEATURES AND PACKAGING ON THE TOTAL SALES OF BATH SOAP PRODUCT - SETIA TJAHYANTI; STEFANI STEFANI; IAN NURPATRIA SURYAWAN (Jurnal Bisnis dan Akuntansi, 2014)
A few things that determine consumer choice of bath soap product is the features and appearance of the product of interest. This research result indicates product packaging is affect campus student in buy bath soap product while features have no influence against purchase bath soap products.